Bringing power to the people or the well-connected? Evidence from Ethiopia on the gendered effects of decentralizing service delivery - Kosec, Katrina; Song, Jie; Zhao, Hongdi (International Food Policy Research Institute, 2020)
Decentralization, or devolution of authority to lower levels of government, is often motivated by its potential to make service delivery more responsive to citizens’ preferences. However, women’s ability to influence policy outcomes may vary across levels of government. This paper considers how decentralization affects both women’s and men’s access to government-provided services and their level of political engagement. We exploit the partial roll-out of decentralization in Ethiopia during 2000–01 and use a spatial regression discontinuity design to identify its impacts. Decentralization improves access to public services for both women and men, but the benefits for men are greater, widening the gender gap in access. We find no evidence that this is due to women’s lower likelihood of participating in local elections; indeed, decentralization increases women’s but not men’s participation. However, decentralization disproportionately increases men’s interactions with local government officials and influential civil society leaders—who wield more power under decentralization. The results are consistent with non-electoral channels of political influence at the local level, dominated by men, contributing to policy outcomes favoring men. They shed light on potential pitfalls of decentralized service delivery from a gender equality perspective, and provide policy recommendations for ensuring women’s equitable access to services.